2019
DOI: 10.1016/j.ccell.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

The ERBB-STAT3 Axis Drives Tasmanian Devil Facial Tumor Disease

Abstract: SummaryThe marsupial Tasmanian devil (Sarcophilus harrisii) faces extinction due to transmissible devil facial tumor disease (DFTD). To unveil the molecular underpinnings of this transmissible cancer, we combined pharmacological screens with an integrated systems-biology characterization. Sensitivity to inhibitors of ERBB tyrosine kinases correlated with their overexpression. Proteomic and DNA methylation analyses revealed tumor-specific signatures linked to the evolutionary conserved oncogenic STAT3. ERBB inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 95 publications
2
38
0
1
Order By: Relevance
“…Also, STAT3 induces the expression of IL-10 and TGF-β1, through direct promoter binding, which ultimately restrains the tumor-suppressive role of CD8 + effector T-cell function and dendritic cells [129,130]. Another important finding revealed that STAT3 sequesters STAT1 through cytoplasmic heterodimerization and hinders STAT1 mediated transcription of major histocompatibility complex (MHC) class I genes [131]. Reduced surface expression of MHC class-I genes in cancer cells pose unfavorable presentation of cancer cells to CD8 + effector cells and thereby diminishing tumor immunosurveillance.…”
Section: Immune Functionmentioning
confidence: 99%
“…Also, STAT3 induces the expression of IL-10 and TGF-β1, through direct promoter binding, which ultimately restrains the tumor-suppressive role of CD8 + effector T-cell function and dendritic cells [129,130]. Another important finding revealed that STAT3 sequesters STAT1 through cytoplasmic heterodimerization and hinders STAT1 mediated transcription of major histocompatibility complex (MHC) class I genes [131]. Reduced surface expression of MHC class-I genes in cancer cells pose unfavorable presentation of cancer cells to CD8 + effector cells and thereby diminishing tumor immunosurveillance.…”
Section: Immune Functionmentioning
confidence: 99%
“…STAT3 and STAT5 are also known to be phosphorylated by several receptor tyrosine kinases (RTK), such as the ErbB family, IGF-1R, or FGFR [109], most of which are HSP90 client proteins. Interestingly, they are also activated or captured for signal transduction by those RTK without phosphorylation [110]. Given their membrane localization, these RTK must go through a complex process of folding, maturation, and membrane insertion that requires significant chaperone cooperation.…”
Section: Hsp90 and Erbb Family Of Receptor Tyrosine Kinase (Rtk)mentioning
confidence: 99%
“…STAT3 is part of the Signal Transducer and Activator of Transcription (STAT) family which includes seven members encoded by distinct genes. STAT3 has evolutionary conserved amino acid sequences between H. sapiens and S. harrisii (99.09%) [1]. In resting cells, STAT3 remains in an inactive form in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, STAT3 in cancer cells affects stromal cells function, establishing crosstalk between cancer cells and its microenvironment. For example STAT3 can dampen STAT1-mediated upregulation of MHC class I, allowing immune escape [1]. The other way for STAT3 to drive tumor immune escape is to regulate the function of stromal cells and more particularly immune cells.…”
Section: Introductionmentioning
confidence: 99%